Umbilical venous blood pH: a useful aid in the diagnosis of asphyxia at birth. Issue 1 (January 1983) - D'Souza, S W; Black, P; Cadman, J; Richards, B
Abstract : Umbilical venous blood, and umbilical arterial blood pH, PO2, PCO2, and base excess were determined in 453 term infants at birth. The results indicate that umbilical venous blood pH, and umbilical arterial blood pH are significantly related to each another. Acidosis, as defined by an umbilical venous blood pH less than 7 X 27, is associated with a lower PO2, a raised PCO2, and a reduced buffer base when compared with PO2, PCO2, and buffer base associated with a normal pH (7 X 27-7 X 42), or alkalosis (pH greater than 7 X 42). The infant's condition at birth was recorded using modified Apgar scores, in which the gradings were vigorous (5-6), intermediate (3-4), or depressed (0-2). In the neonatal period, neurological abnormalities occurred in infants who had been in a depressed condition at birth in the presence of acidosis. Other infants, who had been in a depressed condition with a normal pH or alkalosis and the remaining infants who had an intermediate or a vigorous condition at birth, did not manifest neurological abnormalities in the neonatal period. Our findings suggest that measurement of umbilical venous blood pH, whose values correlate well with those of umbilical arterial blood pH, in infants who are in a depressed condition at birth improves the clinical assessment of the severity of asphyxia.